Analisa Perbandingan Penerapan Airport Sustainability di Bandar Udara Internasional Soekarno Hatta dan Bandar Udara Internasional Schiphol - Faridha Nahar (Research and Development Agency of The Ministry of Transportation, 2013)
The complex activities that occur at the airport lead to several negative impacts, such as air pollution, noise, and high levels of water consumption. If these negative impacts are allowed to happen without any treatment then environmental degradation will be increasingly out of control. Airport sustainability is one of the concepts offered as a solution to overcome or minimize the environmental damage caused by activities that occur at the airport. Although its main focus is on environmental awareness, this concept basically covers three aspects; environmental, economic, and social. Soekarno Hatta International Airport is one of the airports in Indonesia that apply airport sustainability concept. Even though this concept has been implemented since 2009, its implementation has not been maximized so far. This is in contrast to the application of airport sustainability in Schiphol International Airport in the Netherlands that has achieved ACI Europe Best Airport Award. The aim of this study is to provide recommendations in what steps that can be taken by Soekarno Hatta International Airport to make improvements in the application of airport sustainability by comparing the existing application of airport sustainability between Soekarno Hatta International Airport and Schiphol International Airport. Comparisons were made using ten variables grouped into environmental, economic, and social aspects. Based on data collection and analysis conducted, Soekarno Hatta International Airport has to do some improvements as the results, namely fostering good relationship with stakeholders, establishing policies related to airport sustainability concept, and encouraging technology development on airport facilities. Kompleksnya kegiatan yang terjadi di bandar udara menyebabkan beberapa dampak negatif, seperti pencemaran udara, kebisingan, dan tingginya tingkat konsumsi air bersih. Airport sustainability merupakan salah satu konsep yang ditawarkan sebagai solusi untuk mengatasi atau meminimalisasi kerusakan lingkungan yang terjadi akibat aktivitas-aktivitas di bandar udara, meliputi tiga aspek, yaitu lingkungan, ekonomi, dan sosial. Bandar Udara Internasional Soekarno Hatta merupakan salah satu bandar udara di Indonesia yang menerapkan airport sustainability. Penelitian ini bertujuan untuk memberikan rekomendasi langkah-langkah apa saja yang dapat diambil oleh Bandar Udara Internasional Soekarno Hatta untuk melakukan perbaikan pada penerapan airport sustainability dengan cara membandingkan penerapan airport sustainability pada Bandar Udara Internasional Soekarno Hatta dan Bandar Udara Internasional Schiphol. Perbandingan dilakukan dengan menggunakan sepuluh variabel yang dikelompokkan ke dalam tiga aspek, yaitu lingkungan, ekonomi, dan sosial. Berdasarkan pengumpulan data dan analisa yang dilakukan diperoleh hasil bahwa Bandar Udara Internasional Soekarno Hatta harus melakukan beberapa perbaikan, yaitu pembinaan hubungan baik dengan seluruh stakeholders, penetapan kebijakan-kebijakan terkait pelaksanaan airport sustainability, dan pengembangan teknologi pada beberapa fasilitas bandar udara.